2021
DOI: 10.1097/ccm.0000000000005051
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Socioeconomic Status, Patient Risk, and Short-Term Intensive Care Outcomes

Abstract: OBJECTIVES: To investigate the association of socioeconomic status as measured by the average socioeconomic status of the area where a person resides on short-term mortality in adults admitted to an ICU in Queensland, Australia. DESIGN: Secondary data analysis using de-identified data from the Australian and New Zealand Intensive Care Society Centre for Outcome and Resource Evaluation linked to the publicly available area-level Index of Relative Socioec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…A smaller number of studies (n = 10) reported associations between socioeconomic status and ICU length of stay. Six of these demonstrated longer ICU length of stay among patients of lower socioeconomic status (3,7,23,30,35,45), and four found no significant difference (20,39,41,44). Meta-Analysis of ICU Length of Stay.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A smaller number of studies (n = 10) reported associations between socioeconomic status and ICU length of stay. Six of these demonstrated longer ICU length of stay among patients of lower socioeconomic status (3,7,23,30,35,45), and four found no significant difference (20,39,41,44). Meta-Analysis of ICU Length of Stay.…”
Section: Discussionmentioning
confidence: 98%
“…Most studies reporting length of stay associations did so for the full cohort (7, 23, 35, 39, 41, 44, 45). Therefore, paradoxically, an early death in ICU may represent a statistically favorable outcome, limiting the utility of these measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the individual-level, place-level measures, such as those by neighborhood or by city, could prove useful in identifying geographic inequities in critical illness survivorship care and outcomes. One valuable contribution has been the use of regional socioeconomic indexes to quantify an aggregate measure of an area's socioeconomic status (3). These aggregate indices can elucidate general relationships between deprivation and health outcomes, particularly in the absence of individual-level socioeconomic data.…”
Section: Embed Socioeconomic Position In Critical Illness Survivorshi...mentioning
confidence: 99%
“…In contrast, health inequities are the structural or institutional patterns that produce health disparities. In recent studies, critical illness survivors who came from lower socioeconomic backgrounds presented with more severe conditions upon ICU admission (3); had higher in-hospital, 30-day postdischarge, and long-term crude mortality (4); encountered more barriers to a successful ICU discharge (5); and had poorer cognitive and financial outcomes post ICU discharge (6, 7). The common theme among these studies is that there are associations between socioeconomic position and critical illness survivor outcomes, often demonstrating less favorable outcomes in less affluent populations.…”
Section: Critical Illness Survivorship Health Disparities and Health ...mentioning
confidence: 99%